Communicating with providers about racial healthcare disparities: The role of providers' prior beliefs on their receptivity to different narrative frames. Issue 1 (January 2019) - Burgess, Diana J.; Bokhour, Barbara G.; Cunningham, Brooke A.; Do, Tam; Eliacin, Johanne; Gordon, Howard S.; Gravely, Amy; Jones, Dina M.; Partin, Melissa R.; Pope, Charlene; Saha, Somnath; Taylor, Brent C.; et al.
Highlights: We tested whether narratives could engage providers with healthcare disparities. Provider Success narratives led to more participation in training than Provider Bias narratives. Providers' beliefs about disparities affected which narrative they identified with. Abstract: Objective: Evaluate narratives aimed at motivating providers with different pre-existing beliefs to address racial healthcare disparities. Methods: Survey experiment with 280 providers. Providers were classified as high or low in attributing disparities to providers (HPA versus LPA) and were randomly assigned to a non-narrative control or 1 of 2 narratives: "Provider Success" (provider successfully resolved problem involving Black patient) and "Provider Bias" (Black patient experienced racial bias, which remained unresolved). Participants' reactions to narratives (including identification with narrative) and likelihood of participating in disparities-reduction activities were immediately assessed. Four weeks later, participation in those activities was assessed, including self-reported participation in a disparities-reduction training course (primary outcome). Results: Participation in training was higher among providers randomized to the Provider Success narrative compared to Provider Bias or Control. LPA participants had higher identification with Provider Success than Provider Bias narratives, whereas among HPA participants, differences in identification between the narratives were not significant. Conclusions: Provider Success narratives led to greater participation in training than Provider Bias narratives, although providers' pre-existing beliefs influenced the narrative they identified with. Practice implications: Provider Success narratives may be more effective at motivating providers to address disparities than Provider Bias narratives, though more research is needed.